Research Efficiency in Chilean Universities: A Look from Data Envelopment Analysis; [Eficiencia de la Investigación en Universidades Chilenas: Una Mirada Desde el Análisis Envolvente de Datos] - Abello-Romero, J (Pro-Metrics, 2025)
Objective. The objective is to analyze Chilean universities’ efficiency in using some research-related inputs to determine their impact on the results of their scientific production. Design/Methodology/Approach. To achieve the outlined objective, some strategic resources are used as inputs, such as financial income, full-time equivalent academic staffing, and the number of enrolled students, and, as output, the number of publications in journals indexed in the Scopus database between 2020 and 2022. This is a descriptive and quantitative research using the data envelopment analysis technique. Results/Discussion. Valuable information for university management and governance was identi-fied, including that three universities reached 100 % efficiency and seven others exceeded 90 %. The Mann-Whitney U and Student’s t-tests, which show significant and favorable results for public entities, evidence the differences between public and private universities. Conclusion. The analysis suggests that multiple factors should be considered when evaluating the efficiency of academic institutions, especially their context and mission, especially regarding scientific production. © 2025 The author(s).